Musicokinetic and exercise therapies decrease the depression level of elderly patients undergoing post-stroke rehabilitation: The moderating effect of health regulatory focus - Zhao, Li; Lyu, Xiaokang; Jiang, He; Gao, Xinhai (Frontiers in Psychology, 2022)
This study aims to investigate the impact of musicokinetic and exercise therapies on the depression level of elderly patients undergoing post-stroke rehabilitation and its possible moderators, the promotion focus and prevention focus of the health regulatory focus. An eight-week randomized controlled trial was employed. Sixty-five elderly patients undergoing post-stroke rehabilitation in a hospital in Shanghai, China. Patients were randomly assigned to the musicokinetic (n = 32) therapy group or the exercise (n = 33) therapy group. The Mini-mental State Examination Scale measuring the patients’ cognitive functions was used to screen participants. The Hamilton Depression Rating Scale and the Health Regulatory Focus Scale were applied to assess their levels of depression and health regulatory focus on weeks 0, 4, and 8, respectively. The musicokinetic therapy had a significantly better effect than the exercise therapy for individuals who had a lower level of prevention focus, whereas the exercise therapy had a significantly better effect than the musicokinetic therapy for individuals who had a higher level of prevention focus. Musicokinetic therapy and exercise therapy were both effective in decreasing post-stroke depression for elderly patients. But it is important to choose an appropriate type of therapy per the health regulatory focus of elderly patients with post-stroke rehabilitation.